An empirical validation of excellent work culture scales: evidence from selected established higher education institutions in West Malaysia - Musah, Mohammed Borhandden; Mohd Ali, Hairuddin; Vazhathodi Al-Hudawi, Shafeeq Hussain; Hamdan, Abdul Rahim (Canadian Center of Science and Education, 2014)
This study argues that the components of excellent work culture (EWC) since its emergence in the 1980s in the Malaysian public sector were not empirically validated. Therefore, the purpose of this empirical study is to validate instrument and the factor structure of the underlying dimensions of EWC in higher education institutions (HEIs) in West Malaysia. The study sampled 1068 faculty members of eight selected HEIs. The results reveal that the EWC two-factor model fitted the observed data; CFI=.97, TLI=.97, NFI=.97, χ2/df=4.92, RMSEA=.08 and SRMR=.01. Moreover, the results provide psychometric evidence of composite reliability, convergent and discriminant validity of the instrument validated. This study is deemed as an initiative in validating the psychometric properties of the scales. Theoretically, the study has marked a new direction in the positive work culture settings by devising empirical quantitative measures adding to the conceptual body of EWC. Practically, the findings have practical implications for policy makers in the education sector, both public and private with particular reference to establishing a more conducive work environment, which helps workforce performance and productivity at tertiary level to coexist effectively. Keywords: construct validity, content validity, excellent work culture, higher education institutions